Designing the Process of Education and Training of Future Teachers on the Basis of Individual Principles - Ismailova, Zukhra Karabaevna (International Journal of Psychosocial Rehabilitation, 2020)
There are discussed in the article principles of forming for the future teachers skills for personality- oriented education planning. In the article is described necessity of students’s individual features consideration in distribution them to groups with the purpose of development of concrete professional competenses.